Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am learning how to do calculus and was presented with an example I am struggling a bit to understand. Why does $\frac{df}{dx}=3f$ have the general solution of $f(x)=Ce^{3x}$?

share|improve this question
5  
Have you tried differentiating $Ce^{3x}$? –  J. M. Nov 24 '11 at 17:52
1  
I suppose the deeper interpretation of the question is why this ODE only has solution $f(x) = Ce^{3x}$, i.e. why this is the most general possible solution. –  user7530 Nov 24 '11 at 18:00
4  
If we take 7530's "deeper interpretation", note that you can rearrange things as $\dfrac{f^\prime}{f}=3$. Recall that one can logarithmically differentiate: $\dfrac{\mathrm d}{\mathrm dx}\log(f(x))=\dfrac{f^\prime(x)}{f(x)}$... then integrate both sides. –  J. M. Nov 24 '11 at 18:07
1  
@J.M. What happens at the points where $f$ could be 0? For calculus, I preffer the following approach: Let $g(x)= \frac{f(x)}{e^{3x}}$. Then $g'(x)=....$... –  N. S. Nov 24 '11 at 18:29
2  
@J.M. The point I am trying to make is that the problem only gives $f'=3f$. I don't see any obvious reason (at the level of a first year calculus student) to conclude that $f$ is nowhere vanishing....Yes we know the solution is the exponential function, which doesn't vanish, but how can we use that before solving the problem? –  N. S. Nov 24 '11 at 18:50
show 7 more comments

2 Answers 2

up vote 5 down vote accepted

If we are worried about the hazards of division by $0$, let $$g(x)=\frac{f(x)}{e^{3x}}.$$ Differentiate, using the Quotient Rule. We get $$g'(x)=\frac{e^{3x}f'(x)-f(x)(3e^{3x})}{(e^{3x})^2}.\qquad\qquad(\ast)$$ Using $f'(x)=3f(x)$ we can see that the numerator in $(\ast)$ is $0$. So $g'(x)$ is identically $0$, and therefore $g(x)$ is a constant function $C$. Thus $$C=\frac{f(x)}{e^{3x}},$$ and $f(x)=Ce^{3x}$.

share|improve this answer
add comment

You have $ \frac{dy}{dx} = 3y$. Multiply by $x$ and divide by $y$ you'll get $\frac{1}{y}dy=3dx$. By doing integration you'll have: $\int \frac{1}{y}dy=\int3dx$, and after solving the integral you'll have $\log{y} = 3x + c$. By looking at the exponent, you'll get $y = e^{3x}e^{c}$, where $c^{,} = e^{c}$ is a positive constant.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.